Keadilan di Balik Jeruji Kekerasan: Dinamika Putusan Pengadilan dalam Kasus Perceraian Akibat KDRT - Elsa Elvionita, Elsa Elvionita; Zulfan, Zulfan; Elfia, Elfia (Program Studi Magister Ilmu Hukum Universitas Islam Nusantara, 2024)
This research was conducted to examine divorce cases caused by domestic violence and how the courts resolve domestic violence disputes. Uncontrolled anger can trigger violence, including in the context of Domestic Violence (KDRT). This research uses normative juridical methods to explore the role of the court in resolving marital disputes resulting from domestic violence, including legal, psychological and social aspects. Law Number 23 of 2004 concerning the Elimination of Domestic Violence provides a legal framework to protect victims from various forms of domestic violence, such as physical, psychological, sexual violence and neglect. Courts are expected to function not only as places for resolving disputes, but also as institutions that provide justice and protection for victims and play a role in preventing domestic violence in the future. Therefore, the author is interested in studying this issue to understand the role of the courts in handling domestic violence cases and ensuring more effective protection for victims